PENERAPAN EMPAT PILAR PENATALAKSANAAN DIABETES MELLITUS OLEH KADER: STUDI FENOMENOLOGI - Rola Oktorina; Rahmiwati Rahmiwati (Jurnal Endurance, 2021)
Diabetes is a common disease and the incidence is increasing. It is estimated that nearly half of all people (49.7%) living with diabetes are undiagnosed. Community empowerment in increasing early awareness in monitoring risk factors is one of the goals in the control program for non communicable diseases including diabetes mellitus. The purpose of this study was to explore the experience of diabetes cadres in implementing the 4 pillars of diabetes mellitus management. This study uses a qualitative method. The participants in this study were cadres of PTM Puskesmas in Bukittinggi with at least 5 years of experience. Participants were selected by purposive sampling, there were 12 participants. The results of the data analysis process have found several main themes from the experience of DM cadres in implementing the 4 pillars of DM implementation, namely being happy to be of benefit to others, hopes of DM cadres and implementing cadre activities. The implementation of the 4 pillars of diabetes mellitus management at the Bukittinggi city health center has been carried out well. Diabetes cadres have performed duties as an extension of the health center where they live. It is necessary to increase cadres knowledge and motivation of diabetes mellitus sufferers as well as support from families of diabetes mellitus sufferers and the role of diabetes mellitus cadres in implementing the 4 pillars of diabetes mellitus management